Layanan Bantuan Hukum terhadap Kasus Tindak Pidana Pelecehan Seksual di Lingkungan Kampus - Muhammad Rizqi Ardila; Abd. Wachid Habibullah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Sexual harassment cases in university environments have become a serious issue that not only harms victims physically and psychologically but also undermines academic and humanitarian values. This article aims to analyze the implementation of legal aid services in addressing criminal acts of sexual harassment within higher education institutions, particularly in terms of victim protection, legal assistance, and the restoration of victims’ rights. This study employs an empirical or socio-legal approach by examining existing legal regulations and the practical implementation of legal services by campus-based legal aid institutions. The findings reveal that although several universities have established task forces or sexual violence service units, their implementation still faces challenges such as limited resources, low legal awareness, and a prevailing culture of silence among students. Therefore, institutional strengthening, continuous awareness campaigns, and victim-centered campus policies are necessary to ensure comprehensive access to justice. Legal aid services must not only be reactive but also preventive and educational, as part of a broader effort to create a safe and violence-free academic environment.